Diseño e implementación de una estructura de costos estimados y propuesta de un plan de mejoras para incrementar la rentabilidad en la empresa molinera - Hilario Cochas, Katherine Lourdes (2020)
This research job will describe each of the activities preformed at the company “Molino ABC” with the purpose of designing, evaluate and implement an estimated cost structure and stablish an improvement plan to increase profitability. The milling company, specifically the production of wheat flour, have certain difficulties, such as some of the manufacturing industries, to obtain a determination of estimated costs in line for the decision-making of managers, such as: management bulk inventories of wheat and the diversity of products and by-products obtained from the same raw material (wheat). In the first chapter, a brief description of the milling company and the sector is made. Additionally, an approach of the problem is made based in the indicators that are deviated from the objectives that the organization had established, such as the level of profitability at the product level. In the second chapter, the objectives of the investigation, both general and specific, were determined and in the third chapter the scope and limitations of the research were defined, which allowed describing the scope within which the project was carried out, as well the aspects that were included and the aspects that were not taken into account in this investigation. In the fourth chapter, technical, economic and social justifications were established. With them it could be defined if the project is viable as there is a similar process technique in the industry. In chapter five, the proposals for solutions to the problem posed are mention, using the engineering tools to design these solutions. In addition, the results obtained and that will be obtained when implementing the proposed solutions are described.